The Posterior Parietal Cortex Subserves Precise Motor Timing in Professional Drummers - Pollok, Bettina; Stephan, Katharina; Keitel, Ariane; Krause, Vanessa; Schaal, Nora K. (Frontiers in Human Neuroscience, 2017)
The synchronization task is a well-established paradigm for the investigation of motor timing with respect to an external pacing signal. It requires subjects to synchronize their finger taps in synchrony with a regular metronome. A specific significance of the posterior parietal cortex (PPC) for superior synchronization in professional drummers has been suggested. In non-musicians, modulation of the excitability of the left PPC by means of transcranial direct current stimulation (tDCS) modulates synchronization performance of the right hand. In order to determine the significance of the left PPC for superior synchronization in drummers, we here investigate the effects of cathodal and anodal tDCS in 20 professional drummers on auditory-motor synchronization of the right hand. A continuation and a reaction time task served as control conditions. Moreover, the interaction between baseline performance and tDCS polarity was estimated in precise as compared to less precise synchronizers according to median split. Previously published data from 16 non-musicians were re-analyzed accordingly in order to highlight possible differences of tDCS effects in drummers and non-musicians. TDCS was applied for 10 minutes with an intensity of 0.25 mA over the left PPC. Behavioral measures were determined prior to and immediately after tDCS. In drummers the overall analysis of synchronization performance revealed significantly larger tap-to-tone asynchronies following anodal tDCS with the tap preceding the tone replicating findings in non-musicians. No significant effects were found on control tasks. The analysis for participants with large as compared to small baseline asynchronies revealed that only in drummers with small asynchronies tDCS interfered with synchronization performance. The re-analysis of the data from non-musicians indicated the reversed pattern. The data support the hypothesis that the PPC is involved in auditory-motor synchronization and extend previous findings by showing that its functional significance varies with musical expertise.